Knowledge and utilization of preconception care among women in selected community of Kathmandu - Khanal, Laxmi Devi (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Preconception care is a critical component of maternal and child health care services to reduce adverse outcomes of pregnancy and to improve desired health outcomes for women, new-born, and children by focusing on health promotion, screening, and interventions. This study aimed to find out the knowledge and utilization of preconception care among women. Method: A cross-sectional design was carried out among women. Non-probability purposive sampling technique was adopted to select married women of reproductive age in Tokha municipality-10, Kathmandu. Data was collected using face-to-face structured interview. Descriptive and inferential statistics were used to analyze the data. Association among variables was measured by Kruskal–Wallis H test. Result: More than half of the 200 women surveyed, 133 (66.5%) had average level of knowledge and 61 (30.5%) adequate and 6 (3%) inadequate level of knowledge regarding preconception care. Similarly, 196 (98%) had low utilization and 4 (2%) had high utilization level. There was statistically significant association between educational level of respondents with the level of knowledge (p=0.05) and their husband’s educational level (p=0.00). There was no significant association with age, type of family, occupation, monthly family income, number of pregnancy, history of abortion/still birth and age at first pregnancy. Conclusion: This study shows more than half of respondents had an average level of knowledge about preconception care whereas only 2% had high level of utilization of care.